An Analysis of Noun Phrase in the Indonesian Folklore Translated Into English “The Legend of Malin Kundang” On the Indonesian Folklore Website - Hutapea, Parida; Sipangkar, Winda Oktavia; Napitupulu, Glorya Natalia Rohani; Silalahi, Ika Dianda; Sidabalok, Lustriyani (International Journal Corner of Educational Research, 2023)
This research aims to delve into the intricate world of Noun Phrases in the English language, specifically within the Indonesian folklore text, “The Legend of Malin Kundang”, which has been translated into English. Using descriptive qualitative research, researchers sourced text from the Indonesian Folklore website. The enlightening findings of this research revealed a total of 85 Noun Phrases woven into the folklore text. Upon further analysis, thirteen structures emerged, each contributing to the richness and depth of these Noun Phrases. These structures include the combinations of “Article + Noun” (41.18%), “Possessive Adjective + Noun” (17.64%), “Noun + Noun” (14.11%), “Article + Adjective + Noun” (12.94%), “Article + Noun + of + Noun” (2.35%), “Adjective + Noun” (2.35%), “Article + Noun + Noun” (2.35%), “Possessive Adjective + Adjective + Noun” (1.18%), “Article + Pronoun + of + Noun + Noun” (1.18%), “Article + Pronoun + of + Noun” (1.18%), “Pronoun + Noun” (1.18%), “Preposition + Article + Adjective + Noun” (1.18%), and “Article + Adjective + Noun + of + Noun” (1.18%).